2001
DOI: 10.1097/00002030-200108170-00018
|View full text |Cite
|
Sign up to set email alerts
|

Female sex and the use of anti-allergic agents increase the risk of developing cutaneous rash associated with nevirapine therapy

Abstract: To identify factors associated with cutaneous rash, we performed a retrospective multicentre analysis of HIV outpatients starting a highly active antiretroviral therapy regimen containing nevirapine. A total of 62 cutaneous adverse events were observed in 429 patients. Rash hazard was increased in women, by the prophylactic use of glucocorticoids or antihistaminics, and was reduced by escalating the initial dose of nevirapine. Women receiving glucocorticoids had a 3 month cumulative probability of rash of 0.41. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 7 publications
6
47
1
Order By: Relevance
“…Although this study is the first with an unselected outpatient clinic population including both antiretroviral naive and pretreated patients, the observed incidence was comparable to that reported in several clinical trials [9,10,11,12,13,14] and retrospective analyses [16,22,23,24]. Only seven patients (3.2%) in this population discontinued nevirapine because of rash, which is fairly low compared to other studies and reports [9,10,11,12,13,14,16,22,23].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although this study is the first with an unselected outpatient clinic population including both antiretroviral naive and pretreated patients, the observed incidence was comparable to that reported in several clinical trials [9,10,11,12,13,14] and retrospective analyses [16,22,23,24]. Only seven patients (3.2%) in this population discontinued nevirapine because of rash, which is fairly low compared to other studies and reports [9,10,11,12,13,14,16,22,23].…”
Section: Discussionsupporting
confidence: 74%
“…With this strategy the incidence of rash reduced to 9-32% [9,10,11,12,13]. Other strategies that have been evaluated to reduce the occurrence of rashes include the use of corticosteroids and antihistamines as prophylaxis and the use of a slower induction phase of treatment [14,15,16,17]. The use of prophylaxis when initiating therapy with nevirapine remains controversial as contradictory results have been reported [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011) 0.31 0.07 N/A Ugandan (Mukonzo et al, 2009) 0.36 0.10 NA Ghanaian (Bains et al, 2013;Griese et al 1999) 0 that it could be due to differential drug biotransformation, fat content, and exogenous and endogenous hormonal expression differences in males and females (Bersoff-Matcha et al, 2001;Dong et al, 2012;Marinho et al, 2013). Expression of liver enzymes responsible for drug metabolism has also been shown to vary with gender and BMI (Antinori et al, 2001;Bersoff-Matcha et al, 2001). In a comparison between NVP once and twice daily dosing, Schipani et al (2011) reported significantly increased NVP metabolism when body weight increased.…”
Section: Anthropometry Data and Nvp Plasma Concentrationmentioning
confidence: 99%
“…These adverse reactions are more frequent during the first 6 weeks of treatment and women (including those who are pregnant and of Asian ethnicity) seem to be at increased risk of developing NVP-related toxicities (Ho et al, 1998;Antinori et al, 2001;Bersoff-Matcha et al, 2001). Given that immunocompetence is regarded as an additional risk factor for the development of these reactions (De Lazzari et al, 2008), it is recommended that the drug should be initiated in cART-naïve-women with a CD4 cell count below 250 cells/mm 3 and below 400 cells/mm 3 in men (Thompson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%